The Crucifixion of Jesus Torture, Sexual Abuse, and the Scandal of the Cross - Tombs, David (Rape Culture, Religion and the Bible, 2023)
Roman crucifixions sought to degrade and dehumanise their victims in ways that destroyed their dignity and stigmatised their memory. Paul speaks of the cross as a 'scandal' or 'stumbling block', but the significance of this language has never been explored in terms of sexual violence. The Crucifixion of Jesus examines crucifixion as a form of torture, state terror, and sexual abuse. It reads recent accounts of torture alongside the presentation of crucifixion in the Passion narratives and other Greek and Roman sources. Outlining compelling reasons for viewing Jesus as a victim of sexual abuse, it examines why this unsettling aspect of the narrative has remained 'hidden in plain sight' for so long, and what place it might have in discussions of rape culture past and present. It also asks whether other acts of sexual violence and rape might have happened during the mockery in the praetorium, or even on the cross itself. It argues that although the acknowledgement of this 'unspeakable violence' is deeply disturbing, breaking the silence can nonetheless have constructive consequences. In addition to offering a more historical understanding of crucifixion, this book illuminates positive new aspects of resurrection, making it a probing read for scholars of biblical studies and for those interested in the interplay of religion and violence.